Various Errors in English Written Texts Produced by Semester 1 Students of Nursing of Stikes ‘Aisyiyah Yogyakarta in The Academic Year of 2012/2013 - Chahya Kusuma (LITERASI (Jurnal Ilmu Pendidikan), 2017)
This research aims at finding various errors in English written texts pruduced by semester 1 students of nursing of Stikes ‘Aisyiyah Yogyakarta in the Academic Year of 2012/2013.  This research is a descriptive qualitiative research. Sample was taken radomly from 134 texts. The  data in this reseacrh were sentences which have errors.    The result of this research showed seven kinds of errors such as; 1) subject-verb agreement, 2) morphology, 3) diction, 4) preposition and article, 5) mechanics including capitalization and punctuation, 6) frase and sentence composition, and 7) acceptability. There were three factors that cause the errors; language interference, respondents’ limited English grammar understanding and language exposure.  Kata kunci: English teaching in Indonesia, English composition, errors, factor that cause errors